دور التمويل الإسلامي في تطوير المؤسسات الصغيرة والمتوسطة - دية, السعيد; قغيد, ابراهيم; عمارة, لخضر (جامعة الوادي - University of eloued, 2022)
تهدف الدراسة إلى محاولة إبراز إشكالية تمويل المؤسسات الصغيرة والمتوسطة وأهم الإجراءات لدعمها وتطويرها ، من خلال البحث عن بدائل تمويلية تراعي مختلف توجهات وتطلعات أصحاب المشاريع، فانتشر بذلك التعامل بصيغ التمويل الإسلامي التي تقدم صيغ وآليات متعددة ومتنوعة، كأحد أهم وأفضل الأساليب التمويلية المتاحة لتمويل المشاريع الاستثمارية ،بما يضمن نموها وتطورها لتلعب الدور المنوط بها في تحقيق التنمية الاقتصادية والاجتماعية, كما بينت الدراسة الميدانية محدودية مساهمة بنك السلام الجزائري في تمويل المؤسسات الصغيرة والمتوسطة بالجزائر. The study aims to highlight the problem of financing small and medium enterprises And the most important measures to support and develop it, By searching for financing alternatives that take into account the different orientations and aspirations of project owners Thus, dealing with Islamic financing formulas that provide multiple and varied forms and mechanisms has spread, As one of the most important and best financing methods available to finance investment projects, Securing its growth and development and playing the role assigned to it in achieving economic and social development, The field study also revealed the limited contribution of the Algerian Al Salam Bank to financing small and medium enterprises in Algeria.
The role of Islamic finance in developing small and medium enterprises
مقال
Keywords: مؤسسات صغيرة ومتوسطة ; بنوك إسلامية ; تمويل إسلامي